Shifting categories of work: unsettling the ways we think about jobs, labor, and activities - Herzog, Lisa; Zimmermann, Bénédicte (Routledge, Taylor & Francis Group, 2023)
"Shifting Categories of Work illuminates the ways in which our societies categorize work. Written by sociologists, philosophers, historians, and anthropologists as well as management and legal scholars, the contributions in this volume contrast different cultural practices and frameworks of categorizing work"--
Enthält Literaturangaben und Index
Keywords: Aufsatzsammlung; Arbeitspsychologie; Arbeitswissenschaft